Small but Manifold – Hidden Diversity in "Spumella‐like Flagellates". (13th January 2016) - Grossmann, Lars; Bock, Christina; Schweikert, Michael; Boenigk, Jens
Abstract: Colourless, nonscaled chrysophytes comprise morphologically similar or even indistinguishable flagellates which are important bacterivors in water and soil crucial for ecosystem functioning. However, phylogenetic analyses indicate a multiple origin of such colourless, nonscaled flagellate lineages. These flagellates are often referred to as " Spumella ‐like flagellates" in ecological and biogeographic studies. Although this denomination reflects an assumed polyphyly, it obscures the phylogenetic and taxonomic diversity of this important flagellate group and, thus, hinders progress in lineage‐ and taxon‐specific ecological surveys. The smallest representatives of colourless chrysophytes have been addressed in very few taxonomic studies although they are among the dominant flagellates in field communities. To overcome the blurred picture and set the field for further investigation in biogeography and ecology of the organisms in question, we studied a set of strains of specifically small, colourless, nonscaled chrysomonad flagellates by means of electron microscopy and molecular analyses. They were isolated by a filtration‐acclimatisation approach focusing on flagellates of around 5 μm. We present the phylogenetic position of eight different lineages on both the ordinal and the generic level. Accordingly, we describe the new genera Apoikiospumella, Chromulinospumella, Segregatospumella, Cornospumella and Acrispumella Boenigk et Grossmann n. g. and different species within them.